2023
DOI: 10.1039/d2py01217k
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired synthetic polymers-based inhibitors of Alzheimer's amyloid-β peptide aggregation

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease with no cure and limited treatment solutions, wherefore discovering of novel therapies remains a global challenge in biopharmaceutical industries. The pathological hallmark...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…Some examples of diseases caused by protein aggregation include Alzheimer's, Parkinson's, type II diabetes, and prion diseases. [65][66][67][68][69][70] Amyloid fibrillation causing e. g. Alzheimer's or Parkinson's are generally seen as irreversible processes in in vivo conditions. Recently, the thermodynamics of amyloid fibril formation has been increasingly studied in vitro, which has shown that fibril formation is reversible under appropriate conditions.…”
Section: Protein Structure Folding and Misfoldingmentioning
confidence: 99%
See 3 more Smart Citations
“…Some examples of diseases caused by protein aggregation include Alzheimer's, Parkinson's, type II diabetes, and prion diseases. [65][66][67][68][69][70] Amyloid fibrillation causing e. g. Alzheimer's or Parkinson's are generally seen as irreversible processes in in vivo conditions. Recently, the thermodynamics of amyloid fibril formation has been increasingly studied in vitro, which has shown that fibril formation is reversible under appropriate conditions.…”
Section: Protein Structure Folding and Misfoldingmentioning
confidence: 99%
“…Misfolded proteins sometimes can escape these checks, which can lead to protein aggregation, for example in the form of amyloid fibrils, resulting in disease. Some examples of diseases caused by protein aggregation include Alzheimer's, Parkinson's, type II diabetes, and prion diseases [65–70] . Amyloid fibrillation causing e .…”
Section: Proteinsmentioning
confidence: 99%
See 2 more Smart Citations